2020
DOI: 10.1021/jacs.9b13156
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Gels for a Prebiotically Relevant Asymmetric Aldol Reaction in Water: From Organocatalyst Design to Hydrogel Discovery and Back Again

Abstract: This paper reports an investigation into organocatalytic hydrogels as prebiotically relevant systems. Gels are interesting prebiotic reaction media, combining heterogeneous and homogeneous characteristics with a structurally organized active “solid-like” catalyst separated from the surrounding environment, yet in intimate contact with the solution phase and readily accessible via “liquid-like” diffusion. A simple self-assembling glutamine amide derivative 1 was initially found to catalyze a model aldol reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 106 publications
0
50
0
Order By: Relevance
“…Recently, several emerging properties 26,[36][37][38][39][40][41][42][43] of planar fluorophores have been observed in mixed solvents. One of them is supramolecular gelation [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] . It is clear from the gelation table that the gelator is insoluble in water and soluble in DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several emerging properties 26,[36][37][38][39][40][41][42][43] of planar fluorophores have been observed in mixed solvents. One of them is supramolecular gelation [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] . It is clear from the gelation table that the gelator is insoluble in water and soluble in DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Smith et al using a glutanamide derivative (GluC 12 ) to catalyse the aldol reaction between p-nitrobenzaldehyde and cyclohexanone in aqueous solution, observed that reagents addition induced the formation of a gel-like phase (Scheme 7). [19] Deep investigation of the observed phenomenon demonstrated that gel phase resulted from the formation of the reversible imine intermediate between GluC 12 and p-nitrobenzaldehyde. This adduct behaved as a supergelator, being able to induce gel phase formation at concentration lower than 0.1 % w/vol.…”
Section: Organocatalysismentioning
confidence: 99%
“…Based on the design criteria above, we selected our recently disclosed two‐component gelation system ( 1 ) as a potentially suitable LMWG . [ 18 ] This system assembles into gels when a glutamine amide derivative and benzaldehyde are mixed together in a 1:1 ratio, with a reversible reaction between the two‐components giving rise to Schiff base 1 , which is responsible for self‐assembly and gelation ( Figure 1 ). We reasoned this gelator was an ideal candidate for drug delivery applications as the Schiff base should be non‐persistent over long timescales in vivo as a result of hydrolysis, potentially limiting the deposition of any self‐assembled material on repeated administration.…”
Section: Resultsmentioning
confidence: 99%
“…We have also previously shown that gels can still effectively be formed using only 0.7 equiv. of benzaldehyde, [ 18 ] and using this approach, effectively all of the benzaldehyde is immobilized within the solid‐like gel nanofibers. We were therefore comfortable that this two‐component gel constituted a reasonable platform for further investigation as a nasal delivery system and that the impact of benzaldehyde could be minimized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation